THE EFFECT OF THE USE OF POWER POINT LEARNING MEDIA ON MOTIVATION AND COGNITIVE LEARNING OUTCOMES IN SCIENCE LEARNING FOR CLASS IV SDN 39 STUDENTS OFTEN IN SOPPENG DISTRICT - Suriati Suriati; Arsad Bahri; Agustan Agustan (Jurnal Dikdas, 2020)
This study aims to determine the effect of the use of power point learning media on motivation and cognitive learning outcomes in science learning for fourth grade students of SDN 39 Frequently of Soppeng Regency. This type of research is quantitative research that is quasi-experimental design using post-test control group design consisting of experimental class using power point learning media and control class as a class using conventional learning, which is carried out by holding a pretest and posttest in which each The sample is taught with the same material in each sample. The subjects in this study were all class IV which consisted of class IV.a totaling 15 students as an experimental class and class IV.b totaling 15 students as a control class with a total of 30 students. Analysis of the data used is descriptive analysis and inferential analysis using anacova. The results of the analysis showed the average obtained in the pretest motivation of the experimental class learning amounted to 101.2 and the average pretest in the control class was 100.6, and after the treatment was given the results of motivation the experimental class posttest was 105.7 while the posttest results for the control class were 102.8. While the results of the analysis showed the average obtained on the pretest learning outcomes of the experimental class students was 54.33 and the average learning outcomes of the control class pretest students were 51.66. And after being given the treatment of the students' learning outcomes the experimental class posttest was 88 while the control class's posttest result was 78.66. The results of the anakova test of motivation and student learning results obtained p-level values smaller than ɑ 0.05. Thus it can be concluded that there is an influence of the use of power point learning media on motivation and science learning outcomes.